Marmosets as models of infectious diseases - Herron, Ian C. T.; Laws, Thomas R.; Nelson, Michelle (Frontiers in Cellular and Infection Microbiology, 2024)
Animal models of infectious disease often serve a crucial purpose in obtaining licensure of therapeutics and medical countermeasures, particularly in situations where human trials are not feasible, i.e., for those diseases that occur infrequently in the human population. The common marmoset (Callithrix jacchus), a Neotropical new-world (platyrrhines) non-human primate, has gained increasing attention as an animal model for a number of diseases given its small size, availability and evolutionary proximity to humans. This review aims to (i) discuss the pros and cons of the common marmoset as an animal model by providing a brief snapshot of how marmosets are currently utilized in biomedical research, (ii) summarize and evaluate relevant aspects of the marmoset immune system to the study of infectious diseases, (iii) provide a historical backdrop, outlining the significance of infectious diseases and the importance of developing reliable animal models to test novel therapeutics, and (iv) provide a summary of infectious diseases for which a marmoset model exists, followed by an in-depth discussion of the marmoset models of two studied bacterial infectious diseases (tularemia and melioidosis) and one viral infectious disease (viral hepatitis C).